History of Arabic Language Learning: Contemporary Arabic Thought - Qurratul Aini (An Nazhair: Journal of Arabic Education, 2024)
Contemporary Arab thought reflects the efforts of Arab societies to face the challenges of modernity, globalization, and cultural identity. In this era, Arabic thought developed in various fields, including philosophy, politics, religion, and socio-culture. This period was marked by intense interaction between local traditions and modern ideas from the West, which resulted in a wide range of responses, ranging from critical acceptance to resistance. The main challenge of contemporary Arabic thought includes Modernization, namely how to balance traditional values with the demands of modernity. Globalization is Facing global cultural, political, and economic influences that often conflict with local identities. The Identity Crisis is an effort to maintain the Islamic heritage and Arab culture in the midst of social and technological changes. Contemporary Arabic thought has produced various meanings, including Theological Renewal: Through the reinterpretation of more contextual religious texts. Awareness: Strengthening Arab-Islamic cultural identity in the midst of global dynamics. Criticism of Gender Discrimination: Paving the way for gender equality advocacy in Arab society. Global Integration: the longing of Arab societies to participate in global conversations without losing local identity.